Negotiating adolescents' physically active life during the school day - Hoy, Sara; Thedin Jakobsson, Britta; Lunde, Carolina; Larsson, Håkan (Frontiers in Sports and Active Living, 2025)
IntroductionSchool contexts are addressed as important for encouraging adolescents' physically active lives, where whole-school approaches have emerged as globally recognized strategies. Recent research emphasizes the need to further understand the contexts relating to physical activity (PA) and strategies to enhance students' and staff's agency in relation to PA opportunities. In the current study, we explore early adolescent students' daily PA from an ecological perspective, examining the negotiated opportunities and barriers to PA within differing school contexts and how individual agency is expressed in relation to PA.MethodsThis ethnographic collective case study was conducted in four Swedish middle schools that varied in size, resource denseness, and whether they were independent or public providers. The main empirical material was collected through ∼720 h of fieldwork during a school year, along with 86 interviews involving 50 students and 52 staff members. A comparative reflexive thematic analytical approach was used.Results and discussionThe transition between educational stages brought changes that influenced students and staff's agency related to PA. Against this backdrop, the analytical findings were organized into four themes. Students' PA was negotiated against the logic associated with being a “good” middle school student and teacher. Realizing daily PA also stood in relation to an anything-is-possible spirit, which was pitted against the lack of an organizational structure and high hopes for PA outcomes—creating a tension between vision and practicality, where student voices were overlooked. While all four schools claimed a commitment to providing PA opportunities for all, students negotiated their agency based on gender, age, social status, and previous experiences with traditional sports, which dominated recess activities. Students' PA during and after school was closely interconnected, especially expressed in physical education and health classes. This connection often benefited already active students in resource-rich environments while marginalizing those who were less active, further creating an uneven playing field regarding PA opportunities. Various schools shared challenges connected to students' daily PA, but challenges differed between and within schools. Future school policies, practices, and research should aim at addressing cultural, structural, and material dimensions focusing on sustainability, equity, and pedagogical issues, enabling young people to develop autonomy and ability to shape their PA experiences in ways that are meaningful to them.